International Financial Reporting Standards (IFRS) for International Accounting and Financial Integration: with special focus on Wipro Limited of India - Abbasi, Ehtesham Husain (Archives of Business Research, 2016)
ABSTRACT There is a growing international consensus on the International Financial Reporting Standards (IFRS) as acceptable standards for assessment of the financial health of a company across the globe. With the world becoming a global village, companies and investors who operate business in several countries need to understand each nation’s accounting principle. Although basic accounting principles such as the accrual basis and the going-concern assumption are widely accepted, the application of these principles in different economic and cultural environments has led to significant differences as to how accountants report similar transactions. Local differences exist in, for example, the treatment of goodwill, the definition of a group, treatment of borrowing costs, measurement of impairment, and the treatment of deferred taxes. The author considered the Annual reports of Wipro Limited of India. Where in the reconciliation of the equity as per IFRS and Indian Generally Accepted Accounting Principles (IGAAP) were reported for the year beginning 2010 and for the year ended 2011. The 2011-2012 Annual Reports of Wipro presented the consolidated financial statement in both Indian GAAP and IFRS. Reconciliation of equity as per IFRS and IGAAP was reported for the year beginning 2010 and for the year ended 2011, which is considered in this study for examination. Keywords: International Financial Reporting Standards (IFRS), Indian Generally Accepted Accounting Principles (IGAAP), Wipro Limited, International Accounting Standards Board (IASB)